The Narrative Models of the Modern Kazakh Historical Novel - Altybayeva, Saulė (Respectus Philologicus, 2012)
This article considers the various narrative models of the modern Kazakh historical novel and discusses the narrative functions of historical and cultural discourse—the representation of important historical events, the presentation of separate events, the reactualization of the intangible cultural heritage of the Kazakh people. The separate aspects of the nomadic history, culture and philosophy reflected in modern Kazakh historical prose are considered. The inclusion of historical and ethnocultural discourse as the main narrative resource and its aiming at disclosure, an artistic interpretation of events, and the reconstruction of the true history of the Kazakh people—these are among the significant trends of the development of modern Kazakh historical prose. The questions of the artistic coding/decoding of ethnocultural codes and concepts, their deep world outlook, and ontological meanings are investigated. The subjectforming images of legendary historic figures of the nation—Tomiris, Kabanbay Batyr, Abylay Khan, Bukhar Zhyrau, and Tole Biy—as well as those of other nations—Cyrus, Krez, Dariy, and Galden Tseren—are discussed. In aggregate, these images and the related events paint a panoramic historical and cultural portrait of an era in an author’s interpretation. The ethnocultural concepts of tamga and tulpar are investigated, and possible ways of modeling the narrative of Kazakh historical prose are discussed.For the Kazakh novelists, historical events are important both as a truthful reflection of important cultural and historical events and persons, but also, more importantly, as a possibility to reveal spectral problems of universal meaning, philosophical problems of the lives of people, without a strict dependence on the real historical time of action of the novel.Today, the large-scale artistic reconstruction of the national history and culture, the process of the judgment and reconsideration of known historical plots, myths, and legends, are in the mainstream of Kazakh prose. The historical and cultural discourse in the novel assumes a great share of the historical reliability and, at the same time, its exclusive artistic value. The narrative strategies of the Kazakh historical novel assume the wide use of previous mythological and folk traditions, generalizations of the world outlook, and the artistic interpretation of both known and unknown historical events and persons.
Keywords: modern historical novel; historical and cultural discourse; ethnocultural code; concept; narrative; historic figure; narrative models and structures